MENAFSIR KEMBALI KONSEP GRUNDNORM HANS KELSEN DALAM KONTEKS HUKUM DI INDONESIA - Nugraha, Ari; Damanhuri, Tubagus; Siswadi, Gede Agus (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
This research aims to reinterpret the concept of Grundnorm proposed by Hans Kelsen in the context of the legal system in Indonesia. Grundnorm or basic norm is a fundamental idea in Kelsen's pure theory of law, which serves as the basis for the validity of the hierarchy of norms in a legal system. In the Indonesian context, the legal system has its own uniqueness with a strong influence from the principles of Pancasila, customary law, and legal pluralism rooted in society. This research uses a juridical-normative approach with critical analysis of the relevance and application of the Grundnorm concept amidst the dynamics of Indonesian law. The results show that the Grundnorm in the Indonesian context can be interpreted as fundamental values contained in Pancasila, which serves as a constitutional and moral foundation for the national legal system. This interpretation strengthens the argument that Pancasila not only functions as a state ideology, but also as a universal value framework that integrates various elements of customary law, religion, and positive law. As such, this research contributes to the development of modern legal theory discourse by highlighting how local and cultural values can interact with global legal theories, such as the Grundnorm, to create an adaptive and relevant legal system for Indonesian society.